Determination of economic efficiency of deep placement and foliar application of urea fertilizer through the performance of boro rice cv. BRRI dhan29 - Aktar, Tahmina; Rahman, Md Rashedur; Abedin, Md Anwarul; Alam, AHM Jahangir (Research in Agriculture Livestock and Fisheries, 2018)
Rice is the most extensively cultivated cereal crops in Bangladesh and nitrogenous fertilizer, especially urea is the most pressing fertilizer to supply nutrient in the paddy field. With this view, an experiment was conducted to evaluate the effect of deep placement and foliar application of urea fertilizer on BRRI dhan29 rice cultivar in boro season at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during December 2015 to May 2016. The experiment was laid out in a randomized complete block design considering twelve treatments with three replications. The treatments were- T0 ( No N application), T1 [140 kg N/ha (as prilled urea)], T2 (1.8 g 1-USG + 5 foliar spray @ 1% N solution), T3 (1.8 g 1-USG + 5foliar spray @ 1.5% N solution), T4 (1.8 g 1-USG + 5 foliar spray @ 2% N solution), T5 (1.8 g 2-USG), T6 (2.7 g 1-USG), T7 (2.7 g 1-USG + 3 foliar spray @ 1% N solution), T8 (2.7 g 1-USG + 3 foliar spray @ 1.5% N solution), T9 (2.7 g 1-USG + 3 foliar spray @ 2% N solution), T10 (1.8 g 2-USG + 3 t/ha cowdung), T11 (2.7 g 1-USG + 3 t/ha cowdung). Results showed that the grain and straw yield of the rice variety responded significantly to the application of prilled urea (PU), deep placement of USG and foliar application of N. The highest grain yield (4.8 t/ha) was recorded in T8 which was identical to the yield (4.7 t/ha) obtained in T3. The highest straw yield (6.0 t/ha) was found in T5. The lowest grain yield (3.7 t/ha) and straw yield (4.5 t/ha) were found in T0. Considering the economic efficiency, the treatment T8 showed the maximum gross margin and marginal gross margin with lowest cost per unit of product. Therefore, to get highest grain yield (4.8 t/ha), 82 kg N/ha as USG and 3 foliar spray of N @1.5% concentration i.e. total 219 Kg urea/ha can be applied to the rice field of BRRI dhan29. This will save an amount of 81 Kg urea per rice growing season per hectare. Res. Agric., Livest. Fish.5(2): 157-164, August 2018